2016
DOI: 10.1080/15622975.2016.1212172
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between serum brain-derived neurotrophic factor, plasma catecholamine metabolites, cytokines, cognitive function and clinical symptoms in Japanese patients with chronic schizophrenia treated with atypical antipsychotic monotherapy

Abstract: Serum BDNF levels are positively related to the impairment of verbal memory and attention, plasma HVA levels are positively related to motor function, and plasma MHPG levels are positively related to attention in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…In this study, an increased TNF-α level was determined in the patient group, but this difference could not reach statistical significance. Similar to the present study, Hori et al [41] assessed TNF-α levels in clinically stable patients with schizophrenia, and they found no difference compared to healthy controls. There are controversial findings regarding TNF-α levels in patients with schizophrenia [35,42].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, an increased TNF-α level was determined in the patient group, but this difference could not reach statistical significance. Similar to the present study, Hori et al [41] assessed TNF-α levels in clinically stable patients with schizophrenia, and they found no difference compared to healthy controls. There are controversial findings regarding TNF-α levels in patients with schizophrenia [35,42].…”
Section: Discussionsupporting
confidence: 86%
“…In the two studies looking for the correlation of cytokine levels with PANSS scores and cognitive functions in clinically stable schizophrenia patients; the first assessed TGF-β, while the other evaluated IL-6 and TNF-α levels. Both studies showed no correlation of cytokine levels with PANSS scores and cognitive functions [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that plasma MHPG levels were associated with cognitive domains such as verbal learning, working memory, verbal fluency, attention and processing speed, and executive function, suggesting that preserved cognitive functioning in patients receiving aripiprazole may be partly related to activation of the noradrenergic system activation. Indeed, a previous study [22] reported that the plasma MHPG level was associated with attention and processing speed, and that eight weeks of aripiprazole treatment significantly increased plasma MHPG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of schizophrenia have noted that the behavioral response to antipsychotic drugs, such as a decrease in psychosis, parallels a decrease in plasma HVA levels in schizophrenic patients over time [10,11,12,13,14,15,16,17,18,19,20]. Atypical antipsychotics increase the plasma 3-methoxy-4-hydroxyphenylglycol (MHPG) levels and are associated with negative symptoms and cognitive functions [19,21,22]. Brain-derived neurotrophic factor (BDNF) is the most widely distributed neurotrophic factor in the brain, the levels of which have been associated with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of schizophrenia have noted that the behavioral response to antipsychotic drugs, such as a decrease in psychosis, parallels a decrease in plasma HVA levels in schizophrenic patients over time [10][11][12][13][14][15][16][17][18][19][20]. Atypical antipsychotics increase the plasma 3-methoxy-4-hydroxyphenylglycol (MHPG) levels and are associated with negative symptoms and cognitive functions [19,21,22]. Brain-derived neurotrophic factor (BDNF) is the most widely distributed neurotrophic factor in the brain, the levels of which have been associated with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%